Дорадянські документальні листівки як джерело з вивчення втраченої містобудівної спадщини Криму (1895–1917) - Яшний, Д.В. (Праці Центру пам’яткознавства, 2013)
Розглянуто методологічну основу використання дорадянських документальних листівок у вивченні втраченої містобудівної спадщини на основі великого корпусу кримських видів. Проведено аналіз прямий і опосередкованої історіографії, що стала підставою для дослідження: робіт з урбаністичної історії, історії видових листівок, засад дослідження втраченої містобудівної спадщини. Визначено основні дефініції дослідження та критерії їх визначення. Розглянуто питання про поняття «втрачена містобудівна спадщина». Введено в науковий обіг типологію і класифікацію видових листівок, які можуть бути використані у вивченні втраченої містобудівної спадщини. На підставі корпусу кримських документальних листівок, відновлені засади функціонування і співіснування архітектурних елементів різних містобудівних періодів у містах півострова на початок ХХ століття. Рассмотрена методологическая основа использования досоветских документальных открыток в изучении утраченного градостроительного наследия на основе обширного корпуса крымских видов. Проведен анализ прямой и опосредованной историографии, ставшей основой для исследования: работ по урбанистической истории, истории видовых открыток, основам исследования утраченного градостроительного наследия. Определены основные дефиниции исследования и критерии их определения. Подняты вопросы о понятии «утраченное градостроительное наследие». Введена в научный оборот типология и классификация видовых открыток, которые могут быть использованы в изучении утраченного градостроительного наследия. На основе корпуса крымских документальных открыток, восстановлены основы функционирования, и сосуществования архитектурных элементов различных градостроительных периодов в городах полуострова на начало ХХ века. The author examines the methodological basis of the use of pre-Soviet documentaries cards in the study lost urban heritage through an extensive body of Crimean species. The analysis of direct and indirect historiography, which became the basis for the study: works on urban history, the history of postcards, basic research of the lost urban heritage. The basic definition of the study and the criteria for their definition. Raised questions about the concept of «the lost urban heritage.» Introduced into scientific typology and classification of specific cards that can be used to study the lost urban heritage. On the basis of the body of the Crimean documentaries cards, restored basic operation and co-existence of different architectural elements of urban planning periods in the cities of the peninsula at the beginning of the twentieth century. Given the possibility of using postcards to promote the cultural heritage within the «visual turn in Science» with a visual «immersion» reader in the era of the early twentieth century. Appeal to the vast unexplored body graphic sources on the history of the urbanization of the peninsula in the early twentieth century, allows to identify the main trends in the development of urban development in the conditions of self-government of cities. The article is of interest to researchers in the field of source, historic urban planning, culture, historians and anyone who is interested in the history of the Crimea.